Criminalisation of unintentional error in healthcare in the UK: a perspective from New Zealand. (7th March 2019) - Ameratunga, Rohan; Klonin, Hilary; Vaughan, Jenny; Merry, Alan; Cusack, Jonathan
Abstract : Legal reform in New Zealand that saw changes to the prosecution of health professionals for gross negligence manslaughter may have important lessons for the UK in light of the recent case of Hadiza Bawa-Garba, say Rohan Ameratunga and colleagues